Enrolment at the French Navy's School of Advanced Studies in Paris from 1896 to 1899. (3rd July 2021) - Madsen, Chris
ABSTRACT: The navy in France, like several other leading countries in the late nineteenth century, opened a school of higher learning for education of naval officers aspiring to command and staff positions. The School of Advanced Studies came out of a struggle between the ministers and officers supporting the Jeune École and those of a more conventional frame of mind within the naval establishment. The school's background and rationale, as well as a list of naval officers who attended as students in those early years provide a foundation for further comparative research.